Competition Law Issues in the Platform Economy Comparative Commercial and Economic Law Proceedings from the 38th German Conference on Comparative Law in Tübingen - Jung, Peter (Mohr Siebeck, 2024)
The rapidly growing platform economy raises a host of competition law questions worldwide that need to be answered at all levels - nationally, supranationally, and internationally. The issues at stake are expertly examined from comparative perspectives by this volumes international contributors.
PublicationDate: 20240417
Keywords: Missbrauch der Marktmacht von Plattformen -- Kontrolle der Fusion von Plattformbetreibern -- Zugang zu Daten von Plattformen -- Lauterkeitsrechtliche Kontrolle von Plattformbetreibern -- GWB -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Internationales Privatrecht -- Ausländisches Recht, Rechtsvergleichung